Challenges in assessing cardiovascular risk in obstructive sleep apnea-hypopnea syndrome: applicability of existing tools - Stojanović, Milovan; Deljanin Ilić, Marina; Ristić, Lidija; Stamenković, Zoran; Gojković, Dejana; Koraćević, Goran (Vojnosanitetski pregled, 2025)
Background/Aim. Obstructive sleep apnea-hypopnea syndrome (OSAHS) is associated with an increased cardiovascular risk (CVR). The aim of this study was to examine CVR in hypertensive patients with OSAHS using the Systematic Coronary Risk Evaluation 2 (SCORE2), SCORE2-Diabetes, and American College of Cardiology/American Heart Association for atherosclerotic cardiovascular disease (ACC/AHA ASCVD) risk scores. Methods. Due to strict exclusion criteria, out of 410 consecutive OSAHS patients, 92 hypertensive patients with moderate or severe OSAHS were included in the study. All patients underwent CVR assessment using SCORE2, SCORE2-Diabetes, and ACC/AHA ASCVD risk scores. Additionally, all patients, except for seven individuals with extreme obesity (weight over 130 kg) who were unable to perform the test, underwent an exercise stress test, and six of them required further diagnostic assessment using stress echocardiography (three), computed tomography coronary angiography (two), and/or invasive coronary angiography (three). Results. The results showed a substantial burden of moderate to high CVR across all scores. Severe OSAHS was associated with a higher percentage of moderate to high CVR, particularly with the ACC/AHA ASCVD calculator. However, no significant correlation was found between the apnea-hypopnea index and CVR. Furthermore, in three patients, invasive coronary angiography showed multivessel disease requiring myocardial revascularization. Conclusion. General CVR calculators may inadequately represent the specific CVR in OSAHS patients, highlighting the need for tailored risk assessment and increased screening for coronary artery disease in this population. Our results emphasize the clinical relevance of screening for coronary artery disease in individuals with OSAHS.
Keywords: sleep apnea, obstructive; sleep apnea syndromes; coronary artery disease; hypertension; risk factors.